MENINGKATKAN KREATIFITAS MELALUI PELATIHAN KEWIRAUSAHAAN DI SEKOLAH SMK PELITA HARAPAN - Ahmad Ahmad; Yenita Yenita; Kenneth Kenneth; Dian SF; Dharmawan T (PROSIDING SERINA, 2021)
Everyone in the world has talents, interests and hobbies that will provide many benefits if put to good use. After graduating from secondary education, there are several choices that students can take, including working, owning their own business or continuing their education. An entrepreneur is a person who manages and calculates the opportunities and risks of a new or different motivation who must also be able to combine logic and creativity. In this time of Covid 19, the effect has been felt by the community due to the diminishing employment opportunities. For this reason, it is also necessary to motivate efforts to become entrepreneurs so that they accommodate many workers. For this reason, in addition to capital, training is needed to develop an entrepreneurial spirit in the community, including students in areas including SMKS Pelita Harapan in order to understand the process of starting and running a business. The most important purpose of this entrepreneurship training is to help students be able to see business opportunities to be developed and for those who already have a business to always be creative in increasing their business, including developing a business incubator as desired by the school. What is done in this training is to provide theory, application and examples in the form of lectures. In this training, based on the existing potential, it is also taught how to develop a business incubator. From this training, it was found that 93% of the participants gave very good value to the benefits of the training.